1994
DOI: 10.1093/treephys/14.6.563
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal biochemical changes in coniferous forest canopies and their response to fertilization

Abstract: Seasonal changes in concentrations of total nitrogen, free amino acids, chlorophyll, starch and sugar were measured in foliage from fertilized and unfertilized conifer forests in New Mexico and Oregon. In the New Mexico Douglas-fir (Pseudotsuga menziesii var glauca (Beissn.) Franco) forest, fertilization resulted in elevated foliar nitrogen concentrations on all dates, from an average of 9 mg g(-1) in unfertilized trees to 14 mg g(-1) in fertilized trees. In the Oregon western hemlock (Tsuga heterophylla (Raf.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…When buds swell in Douglas‐fir, foliar sugars are metabolized more rapidly than they are produced and therefore tend to be limited (Krueger & Trappe 1967; Billow, Matson & Yoder 1994). The rapid decline in osmotic solute concentration of previous years’ foliage of Douglas‐fir and other evergreen conifers observed during early spring may be a manifestation of this phenomenon and suggests that sugars and other soluble carbohydrates may comprise a significant fraction of cellular osmolytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When buds swell in Douglas‐fir, foliar sugars are metabolized more rapidly than they are produced and therefore tend to be limited (Krueger & Trappe 1967; Billow, Matson & Yoder 1994). The rapid decline in osmotic solute concentration of previous years’ foliage of Douglas‐fir and other evergreen conifers observed during early spring may be a manifestation of this phenomenon and suggests that sugars and other soluble carbohydrates may comprise a significant fraction of cellular osmolytes.…”
Section: Discussionmentioning
confidence: 99%
“…By July, when needles are normally fully expanded, symplast solute content was greater at all heights and increased with height, resulting in a doubling of solute content at 55.6 m between May and July. Billow et al . (1994) found that sugar concentrations of unfertilized Douglas‐fir foliage nearly doubled between May and October…”
Section: Discussionmentioning
confidence: 99%
“…Even though ENF sites exhibited well-defined seasonality in greenness, GCC was only 533 weakly correlated to GPP at these sites. Conifers undergo seasonal changes in chlorophyll 534 content, with winter minima approximately 40% lower than summer maxima (Billow et al 1994, 535…”
Section: Integrated Gcc and Gpp 459mentioning
confidence: 99%
“…Although the higher foliar N concentrations might be associated with higher activity of RuBP carboxylase, which should stimulate light-saturated (darkreaction-limited) photosynthesis (Evans 1989), it is possible that much of the additional N in leaves was in the form of amino acids (Billow et al 1994). Although the higher foliar N concentrations might be associated with higher activity of RuBP carboxylase, which should stimulate light-saturated (darkreaction-limited) photosynthesis (Evans 1989), it is possible that much of the additional N in leaves was in the form of amino acids (Billow et al 1994).…”
Section: Responses Of Individuals To Changes In Soil Resourcesmentioning
confidence: 99%